Optimal Control in Seit Type Epidemic Model with Different Exposed Periods and Saturated Incidence Rates - Trisanti, Yuliana; Mamnunah, Latifatul; Arifin, Mohammad Nazir (International Journal of Trends in Mathematics Education Research, 2024)
The mathematical model of infectious disease spread used in this study is the SEIT (Susceptible Exposed Infective Treatment) type epidemic model with a saturated incidence rate. Optimal treatment control is given to the exposed and infective populations with the same treatment rate with the aim of minimizing the number of infective individuals and treatment costs. By applying the Pontryagin Principle, optimal control and system are obtained. The rate of population change in the model is illustrated by numerical simulations.